1986
DOI: 10.1007/bf01988014
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic histamine release from isolated human basophils during specific immunotherapy

Abstract: Anti-IgE- and antigen-induced histamine release from basophils isolated from 20 atopic patients sensitive to grass pollen allergens was evaluated. The studies were made before and after short-term immunotherapy with Pollinex. It was shown, that after hyposensitization a significant decrease on anti-IgE and specific antigen-induced histamine release from basophils occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It has been shown that the expression of high‐affinity IgE receptors or several function‐molecules on basophils is up‐regulated in allergic patients or after stimulation in vitro in human and mouse studies [ 60–63]. The histamine release from basophils was sometimes decreased after immunotherapy [ 64, 65]. We also found in the C2.0 group that the plasma histamine concentration after antigen challenge was suppressed.…”
Section: Discussionmentioning
confidence: 50%
“…It has been shown that the expression of high‐affinity IgE receptors or several function‐molecules on basophils is up‐regulated in allergic patients or after stimulation in vitro in human and mouse studies [ 60–63]. The histamine release from basophils was sometimes decreased after immunotherapy [ 64, 65]. We also found in the C2.0 group that the plasma histamine concentration after antigen challenge was suppressed.…”
Section: Discussionmentioning
confidence: 50%